Pengaruh Media Pembelajaran Aplikasi Canva Terhadap Minat Belajar Pada Mata Pelajaran Akidah Akhlak Kelas XI di MAN 2 Kota Bogor - Ni’mah, Najihatun; Indriya, Indriya; Triwoelandari, Retno (CV. PUSDIKRA MITRA JAYA, 2025)
Students' interest in learning Akidah Akhlak is often low due to uninteresting learning approaches. Canva application as an interactive visual learning media is considered capable of presenting material in an interesting way and encouraging student involvement. This study aims to determine the effect of Canva learning media on the learning interest of grade XI students at MAN 2 Bogor City. The method used is quantitative with a quasi experimental design of nonequivalent control group design. The research sample consisted of class XI-5 as the control class and XI-6 as the experimental class, each totaling 30 students. The data collection technique was carried out using a learning interest questionnaire which was analyzed by the Paired Sample t-Test and Independent Sample t-Test tests using SPSS version 27. The results of the Paired Sample t-Test test showed a significant increase in student interest in learning after the use of Canva media with a significance value of 0.001 <0.05. While the Independent Sample t-Test results also showed a significant difference between the experimental class and the control class with a significance value of 0.000 <0.05. So the conclusion that can be obtained from the canva application learning media on student learning interest in class XI moral creed subjects at MAN 2 Bogor City is proven to be effective in increasing student learning interest.